Expected and implemented skills, knowledge and attitudes of mentors in the light of Stefan Kunowski's theory of integral development in the opinion of education students - Świdrak, Ewelina; Badora, Anna (Kwartalnik Naukowy Fides et Ratio, 2021)
The main purpose of the presented article is to determine the expected and implemented skills, knowledge and attitudes of mentors, in the opinion of education students and in the light of Stefan Kunowski's theory of integral development.The first part provides a brief overview of the ways mentoring itself is understood. The second part is a theoretical analysis of the mentor's influence in the perspective of the theory of integral development of the Polish educator Stefan Kunowski. The third part presents data obtained as a result of the conducted empirical research. The article ends with main research conclusions.